2018
DOI: 10.1038/s41598-018-34545-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel molecular marker-assisted strategy for production of wheat–Leymus mollis chromosome addition lines

Abstract: Developing wheat–alien chromosome introgression lines to improve bread wheat’s resistance to stresses, such as drought, salinity stress and diseases, requires reliable markers to identify and characterize the alien chromatins. Leymus mollis is a wild relative of bread wheat resistant to salinity and economically important diseases of wheat, but its genome sequence and cytological markers are not available. We devised a molecular marker-assisted strategy for L. mollis chromosome identification and applied it to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…DArTseq technology develops much higher markers with broad genome coverage in compare to the array version of DArT. Therefore, it serves as a cheap alternative tool for genome analysis by whole genome sequencing (Edet et al 2018). These markers have been developed and utilized for genome diversity and genome-wide association mapping in different plant species (Ndjiondjop et al 2017;Pailles et al 2017;Zaitoun et al 2018) and also in wheat (Monostori et al 2017;Alam et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…DArTseq technology develops much higher markers with broad genome coverage in compare to the array version of DArT. Therefore, it serves as a cheap alternative tool for genome analysis by whole genome sequencing (Edet et al 2018). These markers have been developed and utilized for genome diversity and genome-wide association mapping in different plant species (Ndjiondjop et al 2017;Pailles et al 2017;Zaitoun et al 2018) and also in wheat (Monostori et al 2017;Alam et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tzvelev showed about 8 times higher BNI in hydroponic experiments (Subbarao et al 2007). A strong BNI activity of L. racemosus was identified on the L. racemosus 3Ns b (= Lr#n) chromosome in an analysis of L. racemosus chromosome addition wheat lines in which one of the L. racemosus chromosomes was added to wheat (Subbarao et al 2007;Edet et al 2018). Some L. racemosus chromosome translocation lines were developed in which the short or long chromosome arm of 3Ns b was transferred on to the wheat 3B chromosome.…”
Section: Wheat Wild Relatives For a New Trait Of Bnimentioning
confidence: 97%
“…Currently, high-throughput sequencing technology has been widely applied in the development of wild relatives specific markers as their high-efficiency and low-cost, including SLAF-seq ( Chen et al., 2013 ; Zhang et al., 2015 ; Liu et al., 2018 ; Song et al., 2020 ; Wang et al., 2020c ), GBS ( Li et al., 2019a ) and transcriptome sequencing ( Li et al., 2017 ). So far, only two studies have reported the development of markers tightly linked to L. mollis , including 14,530 SNP markers developed based on genome DArTseq ( Edet et al., 2018 ) and 13 DNA markers developed for 2Ns chromosome by SLAF-seq ( Feng et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%